Investigating Factors Related to Easy of Doing Business Score in Asian Countries - Antoine, Niyungeko (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2021)
The objective of this study is to investigate the relationship between ease of doing business score (EDBS) and cost of business start-up procedures (CBS), age dependency ratio (ADR), strength of legal rights index (SLRI), time required to get electricity (TRGE), domestic credit to private sector (DCPS), and start-up procedures to register a business (SPRB). Since 2004, the World Bank evaluates 190 economies based on business regulatory indicators ignoring other factors that may be related to business environment. This paper investigates new factors related to EDBS ignored by the World Bank since 2004. The results of correlation analysis show a negative and significant correlation between EDB and CBS, ADR, TRGE, and SPRB. Nevertheless, a positive and significant correlation was found between EDB and SLRI and DCPS. The linear regression model finds that SLRI and DGPS affected EDB positively and significantly. However, TRGE and SPRB affected negatively to EDB. Asian policymakers should reinforce SLRI and increase DCPS. However, they should also reduce TRGE and SPRB to improve EDB. Further research should be conducted on other regions and test also other factors.